2258. Clinical Predictors of Acute Kidney Injury in HIV Infected Patients Treated With Tenofovir Disoproxil Fumarate (TDF). (26th November 2018) - Holleman, Don; Wagers, Rachel; Thornton, Alice
Abstract: Background: TDF is a nucleotide reverse transcriptase inhibitor used in the management of HIV, Hepatitis B, and in pre-exposure prophylaxis. TDF is potentially toxic to renal proximal tubules leading to overt nephrotoxicity in some recipients. Previous studies have identified risk factors for renal dysfunction in male veterans and Asia. It is unclear if these results generalize to female patients and other ethnic groups. Methods: We conducted a retrospective review of HIV-infected patients treated with TDF in a Ryan White funded clinic at the University of Kentucky which provides HIV care to 1, 600 patients from central and eastern Kentucky. To be included, subjects had to be at least 18 years of age and started a TDF containing regimen between January 1, 2012 and December 31, 2016. Follow-up was through March 2017. We collected demographic and relevant clinical data from the Electronic Medical Record. Acute kidney injury (AKI) was defined as a ≥50% rise in serum creatinine after TDF initiation. Primary outcome was time to AKI using Kaplan–Meier (KM) and Cox proportional hazards analyses. Results: The 660 subjects meeting inclusion criteria were largely male (79.8%) and ethnically white (69.7%), African-American (22.6%), and Hispanic (6.8%). Average age was 41.2 years (SD 11.9 years). During the study period 88 subjects developed AKI. In KM analyses, risk of AKI was greater for females ( P = 0.041), upper tertile of age (>47.5 years, P = 0.024), and among patients with hypertension ( P = 0.001), diabetes mellitus (DM) ( P = 0.02) having detectable HIV viremia ( P = 0.0004) or Hepatitis C viremia ( P = 0.00002). In the Cox model, female sex (hazard ratio [HR]=1.68, P = 0.035), upper tertile of age (HR=1.94, P = 0.026), HTN (HR=1.70, P = 0.023), unsuppressed HIV viral load (HR=2.75, P = 0.00008), and Hepatitis C viremia (HR=2.65, P = 0.0002) increased risk of AKI. Neither ethnicity nor DM were associated with AKI. Conclusion: The factors associated with greatest AKI risk during TDF treatment were hepatitis C viremia and HIV viremia. Older age, female sex, and hypertension were significantly associated with increased AKI. We found neither DM nor ethnicity were independently associated with AKI. Disclosures: All authors: No reported disclosures.